Copper Nanocluster Enables Simultaneous Photodynamic and Chemo Therapy for Effective Cancer Diagnosis and Treatment in Vitro. (1st September 2022) - Joseph, Merin; Pathiripparambath, Muhammed Shafeeque Rahman; Tharayil, Hanas; Jayasree, Ramapurath S.; Nair, Lakshmi V.
Abstract: Metal‐nanocluster‐mediated cancer diagnosis and therapy has drawn considerable attention in recent years due to the unique optical and photophysical properties of metal clusters. This type of material is highly useful for the diagnosis, treatment, and further follow‐up of disease. However, a single treatment modality is not sufficient for a complete cure. The use of a multi‐therapeutic strategy is among the most promising methods for effective treatment, along with an early‐stage diagnosis. To address the multiple therapeutic modalities in a single nanomaterial, a copper nanocluster was synthesized using glutathione, having inherent singlet oxygen generation and emission at 674 nm. A tumor‐targeting agent (folic acid) and an anticancer drug (doxorubicin) was conjugated to the copper cluster for cancer diagnosis via targeted imaging and further double therapy (photodynamic and chemotherapy) in vitro . 10.5 μg (18.1 nmol) of drug conjugated copper cluster shows 56 % cell death for 30 second laser irradiation in HeLa cells. Effective cancer cell imaging and therapeutic efficacy are demonstrated in vitro . Abstract : A drug‐conjugated copper nanocluster (DFaCuC) has great potential for cancer cell imaging and targeted simultaneous double therapy. Inherent fluorescence and singlet oxygen generation of the copper cluster enables imaging and photodynamic therapy. A single system of copper nanocluster facilitates simultaneous targeted imaging and multiple therapy utilizing a conjugated drug molecule (chemotherapy) along with inherent singlet oxygen generation capacity (photodynamic therapy).